Telehealth readiness among Saudi nurses: the critical role of innovative self-efficacy - Abdalmageed Almukalfy; Faizan Kashoo; Jazi S. Alotaibi (Frontiers in Public Health, 2026)
Objectives Grounded in Bandura’s Self-Efficacy Theory and Davis’s Technology Acceptance Model, this study assessed telehealth readiness (TR) and the association with innovative self-efficacy (ISE) among nurses in Al-Madinah Al-Munawwarah, Saudi Arabia, while identifying key demographic and professional correlates. Methods We conducted a multicenter cross-sectional survey among 400 registered nurses from three Ministry of Health hospitals using the Telehealth Readiness Assessment Tool (TRAT) and the Innovative Self-Efficacy Scale (ISES). Group comparisons employed non-parametric tests, and multivariable linear regression examined independent associations after adjusting for demographic and professional covariates. Results Nurses with higher ISE demonstrated substantially greater TR. ISE emerged as the dominant independent correlate of TR in multivariable analysis, suggesting that confidence in creative problem-solving may constitute one of the cognitive resources nurses draw upon when preparing for telehealth adoption. Conclusion ISE is a key correlate of TR, independent of demographic and professional characteristics. These findings extend self-efficacy theory to a mandatory, culturally distinct telehealth adoption context and suggest that training programs should target creative problem-solving alongside technical skills to optimize nursing readiness for digital health transformation in Saudi Arabia.